Delineation of Water Bearing Formations in North Kordofan and West White Nile Area Using Vertical Electrical Sounding (VES) and Borehole Data - A. El Hadi, Mohamed; E. Ibrahim, Abdulla (Gezira Journal of Engineering and Applied Sciences; Vol 13 No 1 (2018), 2018)
The present study was conducted in 2012 to delineate the water bearing formations in North Kordofan and West White Nile areas. Vertical Electrical Soundings (VES) technique data and boreholes information from the study area were used in this study. IPI2Win and Freehand 9.02 software applications were used in this study. The former was used for VES data curves ID interpretation along single profile while the latter was used for drawing purpose. The results of the interpretation indicated that, the study area involves three aquifers: upper, lower and deep aquifers. The upper and lower aquifers locate in Bara Basin and west Kosti Basin whereas the deep aquifer locates in Kosti Basin. The thickness of the upper and lower aquifers together attains 150 m as in Umm Balagi and the thickness of the deep aquifer ranges between 25 to 60 m. The upper and lower aquifers are composed of similar rocks of coarse sand and gravels while the deep aquifer is mainly made up of medium sand. The static water table ranges between 20 m in the northwestern parts to more than 100 m in the southern parts. The mode of occurrence, rocks type, and hydraulic condition of the deep aquifer indicated that the aquifer is not a part of the lower aquifer as believed previously.